Thermal Behavior of an Integrated Square Spiral Micro Coil - Y. Benhadda; A. Hamid; T. Lebey; A. Allaoui; M. Derkaoui; R. Melati (Institute of Advanced Engineering and Science, 2015)
We present in this paper a study on the thermal behavior of a square micro coil that will be integrated in a DC-DC micro converter. The first, we calculate the value of inductance. The second, we descript our micro coil; dimensioning, electrical model, and formula of loss. A buck micro converter schematic simulation coupled with ideal and integrated micro coil was presented. This conceptual model of the buck is best understood in terms of the relation between current and voltage of the inductor. Finely, we determinate a mathematical expression giving the evolution of temperatures in an integrated micro coil using the separation of variables method and a visualization of the thermal behavior is determined in 2D and 3D space dimension using the finite element method. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7361